Sinergisitas Guru Pendidikan Agama Islam dan Orang Tua dalam Pembentukan Perilaku Keagamaan Siswa: Kajian Konseptual dan Teoritik - Melani Ida Marini; Joko Subando (Lembaga Yasin AlSys, 2026)
The formation of students’ religious behavior is a complex and multifactorial educational process; therefore, it cannot be fully realized by schools or families separately. This article aims to conceptually and theoretically examine the synergy between Islamic Religious Education (PAI) teachers and parents in strengthening the formation of students’ religious behavior, particularly in the Madrasah Aliyah environment. This study used a systematic literature review method by integrating Islamic character education theory, family education theory, school-family partnership theory, and Bandura’s social learning theory as the analytical foundation. The results of the study show that structured synergy between PAI teachers and parents, manifested through intensive communication, alignment of goals, shared role modeling, supervision of worship, and periodic evaluation, can provide reinforcement for the internalization of students’ religious values. The dimensions of religious behavior formed include worship behavior (ubudiyah), moral behavior, and socio-religious behavior. However, the implementation of this synergy still faces several obstacles, particularly the influence of digital media, the heterogeneity of family backgrounds, and the limited time of both teachers and parents. The conclusion of this article emphasizes that educational collaboration between PAI teachers and parents plays an important role in the formation of students’ religious behavior. This study contributes to the development of an Islamic values-based school-family partnership model that is adaptive to the challenges of contemporary education.